2019
DOI: 10.1080/20002297.2018.1563409
|View full text |Cite
|
Sign up to set email alerts
|

Tongue coating microbiome data distinguish patients with pancreatic head cancer from healthy controls

Abstract: Background: The microbiota plays a critical role in the process of human carcinogenesis. Pancreatic head carcinoma (PHC)-associated tongue coating microbiome dysbiosis has not yet been clearly defined.Objective: Our aim is to reveal the bacterial composition shifts in the microbiota of the tongue coat of PHC patients.Design: The tongue coating microbiota was analyzed in 30 PHC patients and 25 healthy controls using 16S rRNA gene sequencing technology.Results: The microbiome diversity of the tongue coat in PHC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
99
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(111 citation statements)
references
References 47 publications
9
99
1
2
Order By: Relevance
“…Changes in the availability of oxygen, nutrients, and the pH-mediating effect of saliva [96] can promote the growth of different organisms, and conversely, these organisms can be involved in their own small niche construction [97] via biofilm formation and nutrient metabolism, which can produce effects both within the oral cavity (Table 1, Figure 2) and systemically (Table 2, Figure 2). Some researchers have chosen to study all these niches in parallel to compare them against each other [3,8,9], some have selected individual sites with particular focuses on localized dysbiosis in disease states [98][99][100][101][102][103][104][105][106], and others have used an oral rinse approach to capture an overall view of the oral cavity [10][11][12].…”
Section: The Oral Cavity and Its Microbial Nichesmentioning
confidence: 99%
See 1 more Smart Citation
“…Changes in the availability of oxygen, nutrients, and the pH-mediating effect of saliva [96] can promote the growth of different organisms, and conversely, these organisms can be involved in their own small niche construction [97] via biofilm formation and nutrient metabolism, which can produce effects both within the oral cavity (Table 1, Figure 2) and systemically (Table 2, Figure 2). Some researchers have chosen to study all these niches in parallel to compare them against each other [3,8,9], some have selected individual sites with particular focuses on localized dysbiosis in disease states [98][99][100][101][102][103][104][105][106], and others have used an oral rinse approach to capture an overall view of the oral cavity [10][11][12].…”
Section: The Oral Cavity and Its Microbial Nichesmentioning
confidence: 99%
“…The tongue microbiome was explored in the elderly in Japan because of a potential connection between ingested microbes and pneumonia, which found that samples with worse dental health were enriched in pneumonia-associated bacteria [104]. The tongue was also targeted as a potential segment in diagnostic tools that would perhaps incorporate the microbiomes of the full gastrointestinal tract to detect pancreatic cancer [105]. The palatine tonsils were explored in HIV-infected patients to better understand the oral and systemic complications of the disease, and it was shown that the bacteriome was indeed significantly altered in infected individuals, but the mycobiome was not [106].…”
Section: The Oral Cavity and Its Microbial Nichesmentioning
confidence: 99%
“…The fact that in the pancreatic cancer patient dataset OTUs can be identified that show associations between mouth and gut, as well as between individual oral sites suggests that they may be promising candidates for potential biomarkers. Among these were Fusobacterium and Haemophilus, both oral bacteria recently found to distinguish pancreatic head carcinoma patients from healthy subjects (Lu et al, 2019). Also, species belonging to the genera Fusobacterium and Prevotella (even though the latter was only found to show association between mouth and gut) have been shown to associate with periodontal disease (Chiranjeevi et al, 2014;Chen et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…There is no consensus on how the diversity of the microbiome changes in pancreatic adenocarcinoma. The alpha diversity (Shannon index) of the tongue microbiome increases [86]. In contrast, the saliva microbiome showed no change in alpha diversity, while beta diversity was different between cases and controls [88].…”
Section: The Oncobiome In Pancreatic Adenocarcinomamentioning
confidence: 96%
“…In brief, the oral, gastric, and duodenal flora can colonize the common duct, the bile duct, and the pancreatic duct and, finally, the pancreas itself, as shown in a series of animal and human studies [39,64,66,[69][70][71][72][73][74][75][76][77][78][79][80]. Characteristic changes occur to the oral [63,[81][82][83][84][85][86][87][88] and duodenal microbiome [64] in pancreatic adenocarcinoma. Enterobacter, Enterococcus, and E. coli bactibilia [78] or the colonization of the pancreas [41,65,68,[89][90][91][92][93][94] are risk factors for pancreatic adenocarcinoma.…”
Section: The Oncobiome In Pancreatic Adenocarcinomamentioning
confidence: 99%